Being a midwifery student during the pandemic period: a qualitative research - Yüksekol, Özlem Doğan; Ulucan, Mihriban; Baltacı, Nazlı; Berber, Münevver Aybüke (Tokat Gaziosmanpaşa Üniversitesi, 2022)
[EN] Purpose: This study was conducted to determine the how the education of students studying in the Midwifery department was affected by the Covid 19 epidemic. Material and Method: This research is of qualitative type. The research was conducted in between 26/04/2021-21/05/2021. Its study population included 4th grade students studying in the midwifery department of a university in eastern Turkey and going into clinical practice. The sample of the study consisted of 20 students who continued clinical practice on the specified dates and agreed to participate in the study. The data was collected by online video conferencing with Google Meet or Zoom applications. Results: In the content analysis conducted as a result of the study, three main themes were identified as ‘students' views on the pandemic’, ‘students' views on clinical practices’, students' feelings during clinical practice. While the students described it as a chance to continue clinical practice during the pandemic, they stated that they had the fear of catching covid 19. Some students stated that they had problems in communicating with pregnant women during the practices compared to the pre-pandemic period and that education was negatively affected during the pandemic period. Conclusion: In the study, it was revealed that the students' continued practice during the pandemic period had positive results.

Amaç: Bu araştırmanın amacı Covid-19 pandemisi sürecinde kadın doğum kliniklerinde uygulama yapan ebelik son sınıf öğrencilerinin deneyimlerinin incelenmesidir. Gereç ve Yöntem: Araştırma nitel tiptedir. Araştırma 26/04/2021-21/05/2021 tarihleri arasında yapıldı. Araştırmanın evrenini Türkiye’nin doğusunda bulunan bir üniversitenin ebelik bölümü 4. sınıfta okuyan ve klinik uygulamaya çıkan öğrenciler oluşturdu. Araştırmanın örneklemini ise belirtilen tarihlerde klinik uygulamaya devam eden ve araştırmaya katılmayı kabul eden 20 öğrenci oluşturdu. Veriler, Google Meet veya Zoom uygulamaları online video konferans yapılarak toplandı. Bulgular: Araştırmada yapılan içerik analizi sonucunda, öğrencilerin pandemi hakkındaki görüşleri, öğrencilerin klinik uygulamalar hakkındaki görüşleri, öğrencilerin klinik uygulama sırasında hissettikleri duygular olarak 3 ana tema belirlendi. Öğrenciler pandemi sırasında klinik uygulamaya devam edebilmelerini şans olarak nitelerken, beraberinde covid 19’a yakalanma korkusu yaşadıklarını ifade ettiler. Bazı öğrenciler uygulamalar sırasında pandemi öncesi döneme göre gebelerle iletişimlerinde aksaklıklar yaşadıklarını ve pandemi döneminde eğitimin olumsuz etkilendiğini ifade ettiler. Sonuç: Araştırmada öğrencilerin pandemi döneminde uygulamaya devam etmelerinin olumlu sonuçlar yarattığı ortaya kondu.
Pandemi Döneminde Ebelik Bölümü Öğrencisi Olmak: Nitel Bir Araştırma
Keywords: Primary Health Care; Birinci Basamak Sağlık Hizmetleri